Large Foreign Body in Nose in Adult for a Long Time: A Rare Case - Haq, KM Reza Ul; Tabassum, Refat; Islam, Shoriful; Siddiqui, Asif Imran; Basunia, Mohammad Arman Zahed; Lodi, Russel Ahmed Khan; Paul, Mithun Kumar; Islam, Md Amirul (Delta Medical College Journal, 2019)
Otolaryngologists frequently encounter nasal foreign bodies, particularly among children and mentally retarded patients. Many unusual foreign bodies in the nose have been reported like nuts, plastic toy parts, beads and even button batteries. Several symptoms may be present in the case of a nasal foreign body which includes nasal discharge, epistaxis, infection, halitosis, foul breath or body odour and chronic sinusitis. We present a case of 19 years old girl with left sided nasal blockage, foul smell from left nostril and mouth with occasional nasal bleeding for last 13 years. She was treated conservatively but was not improved. On anterior rhinoscopy some blackish material covered with exudates was revealed which was very foul smelling and bleeds on touch. After nasoendoscopy we suspected that it would be an old foreign body which had already formed rhinolith. The large foreign body was fixed with floor, lateral and medial wall (nasal septum) and was removed by 0˚nasoendoscope and also through oral cavity under general anaesthesia. Delta Med Col J. Jan 2019 7(1): 49-52